Représenter les temporalités : outils et méthodes pour saisir les phénomènes de vacance commerciale - Sylvie Laroche (Développement Durable et Territoires)
This article presents the methodological protocol experimented for a research regarding the temporalities of the retail and their influences within a environment. The investigation is a road infrastructure in the Grenoble metropolitan area. We have chosen to study the morphological, programmatic and landscape qualitifies of the suburbs. In doing so, the goal is to analyze the process of stratifications of the territory and the experiences that one can have in these districts. It is also to identify the spatial characteristics of commercial vacancy which distinguish or homogenize the composition of ground floors in the city.